ABCD1 Gene Mutations in Chinese Patients with ALD - J Gordon Millichap (Pediatric Neurology Briefs)
Thirty-two different ABCD1 mutations were identified by direct sequencing of polymerase chain reaction products in 34 unrelated Chinese X-linked adrenoleukodystrophy (ALD) patients examined at Peking University First Hospital, Beijing, PRC.